The Hopf Bifurcation in a Parabolic Free Boundary Problem with Double Layers (Journal of Partial Differential Equations, 1996)
We consider a parabolic free boundary problem which has a bifurcation parameter and double interfaces. We investigate the sign change in a real part of eigenvalues and the transversality condition as a bifurcation parameter cross the critical value in order to examine the stability of the stationary solutions. The occurence of a Hopf bifurcation will be shown at a critical value.
Keywords: Evolution equation; free boundary problem; parabolic equation; Hopf bifurcation